2021
DOI: 10.1177/0954406221996406
|View full text |Cite
|
Sign up to set email alerts
|

Determination of collapse moment of different angled pipe bends with initial geometric imperfection subjected to in-plane bending moments

Abstract: From the recent literature, it is revealed that pipe bend geometry deviates from the circular cross-section due to pipe bending process for any bend angle, and this deviation in the cross-section is defined as the initial geometric imperfection. This paper focuses on the determination of collapse moment of different angled pipe bends incorporated with initial geometric imperfection subjected to in-plane closing and opening bending moments. The three-dimensional finite element analysis is accounted for geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…28,29 The material considered was Type 304 SS, generally used in the piping system, with a 0.26 Poisson's ratio (γ), yield stress (σ o ) of 271.93 MPa, and Young's modulus (E) of 193 GPa. 17,18,26,28 For the present analysis, the elasticperfectly plastic (EPP) material model was used, which offers a conservative estimation of the FE results and thus is useful from the standpoint of the pipe bend's design. 28…”
Section: Geometrical Parameters and Materials Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…28,29 The material considered was Type 304 SS, generally used in the piping system, with a 0.26 Poisson's ratio (γ), yield stress (σ o ) of 271.93 MPa, and Young's modulus (E) of 193 GPa. 17,18,26,28 For the present analysis, the elasticperfectly plastic (EPP) material model was used, which offers a conservative estimation of the FE results and thus is useful from the standpoint of the pipe bend's design. 28…”
Section: Geometrical Parameters and Materials Propertiesmentioning
confidence: 99%
“…22–24 The circumferential crack ( 2 θ) at the intrados was taken as 0°, 45°, 60°, and 90° for which the corresponding relative crack lengths ( θ/π) were 0, 0.125, 0.167, and 0.25, respectively. 28,29 The material considered was Type 304 SS, generally used in the piping system, with a 0.26 Poisson's ratio 0.25em false( γ false), yield stress ( σ o false) of 271.93 MPa, and Young's modulus ( E ) of 193 GPa. 17,18,26,28 For the present analysis, the elastic-perfectly plastic (EPP) material model was used, which offers a conservative estimation of the FE results and thus is useful from the standpoint of the pipe bend's design.…”
Section: Fe Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is necessary to note that most of the research refers to 90° pipe bends, whereas the pipe bends of different angle are not emphasized under combined loading of internal pressure and bending moment. Recently, present authors (Kumar et al 24 ) reported the outcomes of study on determination of collapse moment of pipe bend of different angles incorporated with initial imperfection under in-plane closing and opening bending moments for unpressurized condition and observed that initial imperfect has significant effect. The pipe bends are subjected to out-of-plane bending moments in many situations, for example, some external connections or attachments of pipe features, live load during maintenance, and repair works.…”
Section: Introductionmentioning
confidence: 99%